The Influence of Adult Attachment on Relationship Quality among Multi-Ethnic Group of Parents with Attention Deficit Hyperactivity Disorder Children - Fatahyah, Yahya; Rizal, Abu Bakar; Nur Fatihah, Mat Yusoff (Faculty of Cognitive Sciences & Human Development UNIMAS, 2016)
This study aimed to explore the influence of adult attachment on relationship quality among parents having children with Attention Deficit Hyperactivity Disorder (ADHD). A correlational research design was used to achieve the research objectives. Sixty eight parents of children with ADHD participated in this study. Two measures were used in this study: the Experience in Close Relationship (ECR) and the Dyadic Adjustment Scale (DAS). The findings indicated that when the anxiety attachment level of the participants was high, the marital satisfaction was low.The findings of this study can make a contribution to those focusing on conflict resolution and marital quality with a deeper understanding on the interpersonal problems in the relationship from attachment theory perspectives. It is suggested that a longitudinal research be conducted in the future with both groups of clinical and community in order to explore how attachment variables can predict relationship adjustment and child adjustment overtime.